First-Order Stratigraphic Boundaries of the Late Cretaceous–Paleogene Retroarc Foreland Basin in Colombia - Carvajal-Torres, Juan; Catuneanu, Octavian; Mora, Andres; Caballero, Victor; Reyes, Martin (Frontiers in Earth Science, 2022)
The present-day Magdalena Valley, Eastern Cordillera and Llanos Basin were part of a regional multiphase basin that started as an extensional basin in the Jurassic, was transformed into a retroarc foreland basin in the Late Cretaceous and subsequently separated into a hinterland and a foreland basin during the late Eocene. The purpose of this study was to establish the stratigraphic boundaries formed during the first-order changes that marked the beginning and the end of the lifespan of the retroarc foreland basin. In the initial stage, the lateral extent along the dip of the major depocenter of the basin was approximately 300-470 km. The Magdalena Valley, Eastern Cordillera and westernmost Llanos Basin comprised this depocenter of the basin. However, the western flank of the Eastern Cordillera and most of the Llanos Basin were uplifting. A late Campanian first-order maximum regressive surface preserved at the base of the retrograding marine facies of the Upper Lidita, Buscavidas and Umir, Guadalupe, and Palmichal units, is the lower boundary of the retroarc foreland sequence. This surface does not extend across the whole basin. In the uplifting areas, subaerial unconformities truncate the middle Campanian rocks. These surfaces compound the lower first-order boundary and its diachroneity is controlled by the northward migration of the orogen. The Teruel, Hoyon, Bogota, Cacho, Socha, Barco and Cuervos formations are truncated by a regional first-order subaerial unconformity formed during orogenic unloading that marks the termination of the foreland basin in the Eocene. Therefore, it is the upper boundary of the first-order sequence.